2009
DOI: 10.1371/journal.pone.0006796
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Gene Regulation by the Transcription Factor PPARα between Mouse and Human

Abstract: BackgroundStudies in mice have shown that PPARα is an important regulator of hepatic lipid metabolism and the acute phase response. However, little information is available on the role of PPARα in human liver. Here we set out to compare the function of PPARα in mouse and human hepatocytes via analysis of target gene regulation.Methodology/Principal FindingsPrimary hepatocytes from 6 human and 6 mouse donors were treated with PPARα agonist Wy14643 and gene expression profiling was performed using Affymetrix Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
263
3
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(298 citation statements)
references
References 58 publications
26
263
3
6
Order By: Relevance
“…4B and 7). Consistent with the immunoblot results were no meaningful differences in the mRNA levels of the PPAR target genes CPT1, MCAD, AOX and FABP1 [22][23][24][25], the PPAR/ target genes pyruvate dehydrogenase kinase (PDK) 4 and angiopoietin-like protein 4 (ANGPTL4) [26,27], or the PPAR target genes FABP4 and fat-specific protein 27 (FSP27) [28,29] among the groups ( Fig. 2 and Supplementary Fig.…”
Section: Hepatic Expression Of Ppars and Rxrsupporting
confidence: 72%
“…4B and 7). Consistent with the immunoblot results were no meaningful differences in the mRNA levels of the PPAR target genes CPT1, MCAD, AOX and FABP1 [22][23][24][25], the PPAR/ target genes pyruvate dehydrogenase kinase (PDK) 4 and angiopoietin-like protein 4 (ANGPTL4) [26,27], or the PPAR target genes FABP4 and fat-specific protein 27 (FSP27) [28,29] among the groups ( Fig. 2 and Supplementary Fig.…”
Section: Hepatic Expression Of Ppars and Rxrsupporting
confidence: 72%
“…It has subsequently been found to serve as a coactivator of PPAR ␣ and is therefore involved in the transcriptional control of the genes encoding enzymes of fatty acid oxidation ( 29 ). PPAR ␣ , which is highly expressed in the liver, coordinates transcriptional activation of peroxisomal fatty Acox1 ( 30 ) and CPT1A ( 31,32 ). In the current study, Rb1 signifi cantly increased the activity of CPT1 ( Fig.…”
Section: Downloaded Fromsupporting
confidence: 53%
“…The current study demonstrated that MLE induced up-regulation of gene expression and/or protein level of PPARa and UCP2 in liver. PPARa and UCP2 are associated with lipid homeostasis and energy expenditure by regulation of energy metabolism and mitochondrial b-oxidation (Rakhshandehroo et al 2009). The results suggest that the MLE administration can alter energy metabolism and mitochondrial b-oxidation of long-chain fatty acids via regulation of PPARa and UCP2.…”
Section: Discussionmentioning
confidence: 99%